Penanaman Pendidikan Agama Islam Syekh Magelung Sakti di Desa Karangkendal Kecamatan Kapetakan Kabupaten Cirebon - Mi’roji, Anwar; Fitriyanto, A Alvian; Alawiyah, Tuti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Islamic religious education in society is very important, through education and teaching has an impact on good morals. Religious teachings are not just rituals but up to the actualization of religious teachings and values in everyday life. The arrival of Islamic teachings to the Cirebon area was also initiated by scholars centered in the Muara Jati area. The spread of Islam in the North Cirebon area is also one proof of the success of the spread of Islam by Sheikh Syarif Hidayatullah, according to the story of the Cirebon chronicles, at one time there was a young man named Syarif Sham who had long hair that touched the ground and wanted to find someone who could cut his hair, In short, through the veil of his dream he was shown that there was a Waliyullah in the Cirebon area who was able to cut his hair, and from here he met Sunan Gunung Jati, and finally Syarif Hidayatullah was able to cut Sheikh Magelung Sakti's hair where the place to cut Sheikh Magelung Sakti's hair was called Karanggetas. After studying with Sunan Gunung Jati in Cirebon, Syarif Hidayatullah or Sheikh Magelung Sakti was given the task of developing Islam in the northern region. He then lived in Karangkendal village, Kapetakan sub-district, Cirebon regency until the end of his life, so he was known as Pangeran Soka Karangkendal. The purpose of this research is to obtain data about the Cultivation of the Spread of Islam by Sheikh Magelung Sakti in Karangkendal Village, Kapetakan Subdistrict, Cirebon Regency and correlate it with Islamic Religious Education today. The method in this study uses descriptive qualitative research with the type of field research (field reseacrh), the data source of this study consists of primary data, namely historians, sacred key teachers and Islamic Religious Education (PAI) teachers and secondary data writings related to the discussion of research, namely the Cultivation of the Spread of Islam by Sheikh Magelung Sakti.